Determinan Pertumbuhan Ekonomi Negara ASEAN: Model Data Panel - Wau, Taosige; Sarah, Umi Mai; Pritanti, Diana; Ramadhani, Yesi; Ikhsan , Muhammad Saiful (Fakultas Ekonomi Universitas Samudra, 2022)
The study aims to analyze the effect of inflation, exchange rate, investment, and labor force participation on the economic growth of member countries in the ASEAN region. This study uses secondary panel data, namely economic data from ten ASEAN member countries from 2000-2020. Sources of data obtained from the publications of the World Bank. The analytical method used is the panel data regression method fixed-effects model approach with a SUR cross-section weighted. This study indicates that the increase in inflation, investment, and labor force participation can encourage economic growth in the ASEAN Region. Meanwhile, the weakening of the value of the domestic currency (depreciation) has corrected the economic growth of ASEAN member countries.